Perceived Stress Can Mediate the Associations between a Lifestyle Intervention and Fat and Fast Food Intakes - Chang, Mei-Wei (Nutrients, 2020)
This secondary analysis study addressed a gap of knowledge: whether perceived stress reduction created by a lifestyle intervention might serve as a mediator for reducing fat and fast food intakes in low-income overweight or obese mothers of young children. This analysis included 338 low-income overweight or obese mothers of young children who completed a phone interview immediately after the 16-week lifestyle intervention. Valid surveys were used to assess perceived stress and fat and fast food intakes. Composite indicator structural equation modeling was performed to test the mediation effects. The overall effect of the intervention was not significant for fat intake but was significant for fast food intake (B = −0.53, p < 0.05). When assessing the potential role of perceived stress as a mediator, the indirect effects of the intervention on fat (B = −0.39, p < 0.01) and fast food (B = −0.27, p < 0.01) intakes were both significant. Future dietary intervention studies aimed to reduce fat and fast food intakes in low-income overweight or obese mothers of young children might consider including practical strategies aimed at reducing perceived stress.